Promotion and Education on The Prevention of Juvenile Delinquency From a Health Perspective for Youth Members of Youth Organizations Karang Taruna - Gusgus Ghraha Ramdhanie; Bambang Aditya Nugraha (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Adolescence is a transitional phase from childhood to adulthood. Adolescence needs to be accompanied in such a way because adolescents are still looking for their identity. Drinking alcohol and smoking are considered commonplace behaviors for adolescents, whereas in fact, if this is not properly supervised, it will be very prone to falling into juvenile delinquency. Based on the results of the study, problems that occur in adolescents were identified, namely the high smoking behavior and consumption of alcohol in adolescents. As an effort to overcome these problems, promotional and educational activities related to "Prevention of Juvenile Delinquency" were given to youth members of youth organizations in Jayaraga Village, Tarogong Kidul District, Garut Regency. The community service activity method uses three phases which include needs analysis, implementation, and evaluation. The results obtained from this promotion and education activity are the increased knowledge of participants related to the impact of delinquency on adolescents, based on the results of the post-test analysis that has been done by the promotion and education participants. It is hoped that after this promotion and education activity, the participants can maintain their relationships and the surrounding environment and can share the knowledge they have gained with teenagers who have not had the opportunity to attend promotion and education or other people around them.